Transport Infrastructure, City Productivity Growth and Sectoral Reallocation : Evidence from China - Yang, Yang (IMF Working Papers; Working Paper ;, 2018)
This paper examines the impact of highway expansion on aggregate productivity growth and sectoral reallocation between cities in China. To do so, I construct a unique dataset of bilateral transportation costs between Chinese cities, digitized highway network maps, and firm-level census. I first derive and estimate a market access measure that summarizes all direct and indirect impact of trade costs on city productivity. I then construct an instrumental variable to examine the causal impact of highways on economic outcomes and the underlying channels. The results suggest that highways promoted aggregate productivity growth by facilitating firm entry, exit and reallocation. I also find evidence that the national highway system led to a sectoral reallocation between cities in China.